Eurytrema coelomaticum natural infection in small ruminants: a neglected condition - Ribeiro de Sousa, Davi Emanuel; Gaudencio Barbosa, Edson de Figueiredo; Wilson, Tais Meziara; Machado, Mizael; Oliveira, Wilson Junior [UNESP]; Duarte, Matheus Almeida; Scalon, Marcela Correa; Lopes Camara, Antonio Carlos; Lux Hoppe, Estevam Guilherme [UNESP]; Paludo, Giane Regina; Melo, Cristiano Barros de; Castro, Marcio Botelho de (Cambridge Univ Press, 2021)
Pancreatic eurytrematosis (PE) is an under diagnosed and neglected parasitosis in goats and sheep in the Americas. Clinical and pathological features of PE are not well defined in small ruminants worldwide. Natural cases of PE in small ruminants were detected in the Federal District, Brazil. A survey of necropsy records, including epidemiological and clinicopathological data, in goats and sheep was conducted. Most cases of PE occurred during the rainy season in adult females, with an incidence of 12.9% in goats and 0.8% in sheep. Clinical signs varied from asymptomatic infections to anorexia, lethargy, weakness, marked weight loss and death in some goats. Overall, most cases of PE in goats and sheep were incidental necropsy findings with minor pancreatic lesions. Three goats, however, showed severe chronic pancreatitis, dilation of major pancreatic ducts with numerous trematodes present and marked abdominal fat necrosis. Morphological and molecular characterization of flukes detected Eurytrema coelomaticum. Our findings shed light on the prevalence of E. coelomaticum infections in small ruminants in the region and highlight the possibility of severe and lethal cases in goats. PE must be further investigated in small ruminant populations in relevant livestock production regions of the Americas.
Keywords: Eurytrematosis; fat necrosis; goat; pancreas; sheep; trematode